Epigenetic Therapy in Lung Cancer - Liu, Stephen V.; Fabbri, Muller; Gitlitz, Barbara J.; Laird-Offringa, Ite A. (Frontiers in Oncology, 2013)
Epigenetic dysregulation of gene function has been strongly implicated in carcinogenesis and is one of the mechanisms contributing to the development of lung cancer. The inherent reversibility of epigenetic alterations makes them viable therapeutic targets. Here, we review the therapeutic implications of epigenetic changes in lung cancer, and recent advances in therapeutic strategies targeting DNA methylation and histone acetylation.